The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00520-017-4022-z
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study examining the prevalence of cachexia and areas of unmet need in patients with cancer

Abstract: Cachexia is a prevalent condition, affecting both patients with localized and metastatic cancer. Clinical attention to the condition is a sizeable unmet need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 30 publications
0
55
0
1
Order By: Relevance
“…Ethnicity, age, age by days, and primary cancer site, itself, did not significantly predict weight loss. Female patients had consistently significantly lower weight than male patients, and male patients asked more frequently for information about weight loss and nutrition than did their female counterparts . Results also indicated that patients were similar in weights regardless of primary cancer site at the beginning of the observation period; however, the amount of weight loss gradually differed among cancer patients according to interaction between primary cancer sites and days.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Ethnicity, age, age by days, and primary cancer site, itself, did not significantly predict weight loss. Female patients had consistently significantly lower weight than male patients, and male patients asked more frequently for information about weight loss and nutrition than did their female counterparts . Results also indicated that patients were similar in weights regardless of primary cancer site at the beginning of the observation period; however, the amount of weight loss gradually differed among cancer patients according to interaction between primary cancer sites and days.…”
Section: Discussionmentioning
confidence: 87%
“…In this study of natural weight loss patterns among patients with GI cancers, unintentional weight loss, or cachexia, was significant. Cancer cachexia varies, based on cancer type, 17,18 site, and stage 17 ; however, it is prevalent in patients with either localized or advanced cancers. 18 In our cohort, weight loss was significantly impacted by days of observation (from the first entry), female gender, cancer stage, and primary cancer site.…”
Section: Discussionmentioning
confidence: 99%
“…(6) Cancer cachexia occurs in up to 80% of patients with advanced malignancies and is a contributing factor to mortality. (7) Chemotherapy drugs are used to combat solid tumors, but many of these drugs have significant side effects that contribute to cachexia. (8) Carboplatin is a platinum-based chemotherapy drug used to treat a variety of cancers in both a neoadjuvant and adjuvant setting (9) by interfering with DNA replication and inducing cell death.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] Based on the most recent consensus definition, the prevalence of cancer cachexia is strongly related to cancer type, being highest in lung cancer (83%), and gastrointestinal cancers (62%) and lowest in hematologic cancers (13%). [ 16 ]…”
Section: Cancer Cachexiamentioning
confidence: 99%